PENGARUH HARGA EKSEKUSI DAN JUMLAH OPSI SAHAM KARYAWAN (ESOP) PADA KINERJA PERUSAHAAN - Indah Kartikasari, A.A.Ayu; Putra Astika, Ida Bagus (E-Jurnal Akuntansi; Vol 11 No 3 (2015), 2015)
Operations of the company are not separated from the principal that the contract between the owner of the company and the agents are employees of the management company. In the course of this contractual relationship often cause problems (conflicts), because of differences in the interests of each of these elements. Factors which often triggers the conflict is the imbalance of information. Principal tackle the problem by creating policies that create a more cooperative agent in conveying information on the conditions of the company. One such policy is that ESOP is an employee stock ownership program that is expected to increase the sense of belonging that can trigger the transparency of information from the employees and ultimately will support the improvement of the performance of the company. This research was conducted on the adoption of the ESOP companies listed on the Stock Exchange from 2000 until 2012. The tests were conducted by using path analysis. The sampling method using purposive sampling method and sample obtained by 43 companies from 53 companies. The analysis showed that the price of execution positive effect on firm performance, in contrast to the number of employee stock options (ESOP) negative effect on the performance of the company.
Keywords: Execution price; Number of Employee Stock Option Plan (ESOP); and Company Performance